2020
DOI: 10.1088/1742-6596/1436/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Design of low-flow oxygen monitor and control system for respiration and SpO2 rates optimization

Abstract: The importance of respiration rates and oxygen saturation (SpO2) monitoring and the high need for oxygen therapy opens the opportunity for the development of non-invasive respiration rate and oxygen saturation monitoring and controlling system. There are two modes of controlling in this system, automatic and manual mode. In automatic mode, the oxygen flow rate is based on the measurement of the respiration rate using the MLX90614 temperature sensor and tidal volume determination based on the patient’s body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Based on M. Syahrul Azam [25], the results of his research obtained the error value of the highest SpO2 sensor of 0.68% and the smallest 0.17%. While other similar studies stated the error value in the range of 0.0123% [26], 1% [27], >3% [28], 0.38% [29], 0.81% [30], 1% [31], and other study revealed deviation value approximately 1.62% [32].…”
Section: Discussionmentioning
confidence: 78%
“…Based on M. Syahrul Azam [25], the results of his research obtained the error value of the highest SpO2 sensor of 0.68% and the smallest 0.17%. While other similar studies stated the error value in the range of 0.0123% [26], 1% [27], >3% [28], 0.38% [29], 0.81% [30], 1% [31], and other study revealed deviation value approximately 1.62% [32].…”
Section: Discussionmentioning
confidence: 78%
“…Only those parameters that can operate as consistent, reliable parameters should be considered when deciding which to use for measurement. Based on these and other studies, the following variables were chosen: heart rate [ 63 , 71 , 72 ], blood oxygen saturation [ 64 , 76 ], depth of immersion [ 70 ], pattern of movement [ 73 ], and body temperature [ 77 , 78 ]. All the mentioned factors are reliable, with values that may vary from person to person but stay within a stable range.…”
Section: Sensor-based Techniques For Drowning Detectionmentioning
confidence: 99%
“…SpO 2 is of extreme importance, as if its level drops below a certain value, the body will be unable to carry out its normal functions. The normal range of oxygen saturation in the human body is a consistent value of 95-100% [26], and any values below this number will be considered as a sign of hypoxia. Predictably, when a person is undergoing the process of drowning, his or her oxygen level will fall dramatically, so the oxygen level in the individual's bloodstream is a suitable indicator of whether individuals are experiencing suffocation from drowning.…”
Section: Blood Oxygen Saturationmentioning
confidence: 99%